1998
DOI: 10.1074/jbc.273.6.3635
|View full text |Cite
|
Sign up to set email alerts
|

Casein Kinase II Stabilizes the Activity of Human Topoisomerase IIα in a Phosphorylation-independent Manner

Abstract: Previous reports have indicated that topoisomerase II (topo II) co-purifies with and is a substrate for casein kinase II. We have carried out a detailed study of the effect that purified casein kinase II has on the activity of purified recombinant human topo II␣. Co-incubation of topo II␣ and casein kinase II led to an apparent activation of the topo II␣; however, in experiments in which topo II␣ was preincubated at 37°C with or without native casein kinase II prior to assaying for decatenation activity, it em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 47 publications
1
33
0
2
Order By: Relevance
“…This did not affect the catalytic activity (results not shown), in agreement with results reported by others (51,52). More surprisingly, dephosphorylation of topoisomerase II␣ by phosphatase (Fig.…”
Section: Identification Of Regions Likely To Contain the Mpm-2 Phosphsupporting
confidence: 82%
“…This did not affect the catalytic activity (results not shown), in agreement with results reported by others (51,52). More surprisingly, dephosphorylation of topoisomerase II␣ by phosphatase (Fig.…”
Section: Identification Of Regions Likely To Contain the Mpm-2 Phosphsupporting
confidence: 82%
“…In fact, topoisomerase II␣ activity was enhanced following incubation with low concentrations of glycerol in the absence of kinase, suggesting that the activation mechanism involves topoisomerase autoactivation independent of CKII. A second study found that preincubation with CKII protected topoisomerase II␣ from thermal inactivation and that the apparent activation by CKII was actually due to stabilization against activity loss during the preincubation (43). This protective effect was specific for CKII and could be ascribed to stable interactions previously demonstrated between kinase and topoisomerase II␣ (4), suggesting a potential physiological role for kinase-topoisomerase interactions.…”
Section: Discussionmentioning
confidence: 88%
“…In the case of CK2 and topoisomerase II␣, there is additional complexity because our results demonstrate that both of these proteins can interact with Pin1. Furthermore, several studies have demonstrated that CK2 physically interacts with topoisomerase II in mammalian cells and in yeast, although controversy regarding the relationship of CK2 to the regulation of topoisomerase II remains (31)(32)(33)(34)(61)(62)(63). Clearly, additional studies beyond the scope of this present work will be required to fully illuminate the precise role of Pin1 in the regulation of CK2 and topoisomerase II␣.…”
Section: Discussionmentioning
confidence: 91%